Exploring Gamification’s Role in Shaping Socially Sustainable Urban Spaces: A Case Study of Gensen in SOLANA, Beijing - Yanhua Yao; Zheyu Li; Sai Ma (Buildings)
This paper explores the innovative integration of digitalization and gamification in urban design to address social sustainability challenges in rapidly evolving cities. Using Gensen, a metaverse platform launched in 2024, as a case study, the research investigates how the convergence of virtual environments and real urban spaces can foster new forms of social interaction, spatial usage, and community engagement. The motivation behind this study is to assess the potential of gamification in enhancing social sustainability within digitalized urban contexts. By introducing the opening event, “Treasure Hunting”, established by Gensen, the study examines how users engage with existing urban settings through a gamified approach. The research investigates how gameful design, facilitated by digitalization, can transform public spaces into more dynamic environments that encourage diverse participation while also addressing emerging risks such as spatial inequality resulting from varying levels of access to digital tools and literacy. The research questions focus on how gamification can bridge these gaps and contribute to creating more inclusive urban environments. In conclusion, the study argues that current gamified design approaches, based on digitalization, often overlook the playfulness inherent in physical environments and human interaction. However, a bottom-up approach that emphasizes individuals’ understanding of the inherent playfulness in existing urban spaces is still lacking. This aspect needs further exploration to inform and enhance gameful design strategies aimed at promoting social sustainability in urban development. Bridging this gap is essential for integrating digital interventions into everyday life, ultimately achieving a more effective gameful design in urban contexts.